The Notion of Tax-Havens in the Context of Tax Optimisation of Polish Companies - Pach, Janina (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2019)
Tax havens are highly controversial, first of all with respect to the decrease of the state budget revenues coming from corporate income tax (CIT) and personal income tax (PIT). Many companies, however, locate their business activity outside the territory of their own country thus decreasing their tax liabilities, which leads to the reduction of their own running costs and the possibility of pursuing some other objectives. The aim of the paper is to find an answer to a number of research questions, including: -what is tax optimising and what does it involve? -what is the genesis of tax havens and what are their types? -when are tax havens a legal tool for tax optimising? -to what extent do the Polish companies use tax havens for tax optimising? -what actions are undertaken in Poland in order to rationalise the use of tax havens by Polish entrepreneurs? The answers given in the study will allow to discern between ways of optimisation, including tax frauds, and legal activities aimed at tax optimizing. This distinction will provide the context for the analysis of the practices of locating the activity of some companies in selected countries referred to as tax havens.